Red Data Book 2004 of Vietnam - Thanh, Dang Ngoc (Academia Journal of Biology, 2006)
Contributing to the national biodiversity action plan of Vietnam, the new Red species List and Red Data Book 2004 of Vietnam have been compiled by the Vietnam Academy of Science and Technology, with the participation of 70 scientists from different ministries and agencies of the country. This new Red Data Book 2004 was a revised and updated work, based on the first Red Data Book of Vietnam, published in 1992 (animal part) and 1996 (plant part), using the IUCN Red List Criteria and Categories 1994, updated by new materials of the fauna and the flora of Vietnam, collected in last 10 years. The new Red Data Book 2004 has showed a new situation of the biodiversity of the country after 10 years. The number of threatened species has remarkably increased, from 709 species recorded in the Red Data Book 1992-1996 to 857 species in the Red Data Book 2004. Six animal species were considered as extinct (EX) and extinct in the wild (EW). At the same time, 149 animal species were classified in the endangered category (EN); among them, 46 species were critically endangered (CR). The correspond numbers in plants were 192 endangered species and 45 critically endangered species. The present status of the wild life in Vietnam was caused firstly by the non rational over exploitation in land, as well as in seawaters. Besides, the heavy destruction of the natural environment conditions, including the habitat of wild animals and plants, especially the forest devastation in mountainous regions, the uncontrolled destruction of coral reefs in coastal zone, were also important agents for the degeneration of the biodiversity. In this book, for each animal and plant, suitable protection, conservation and regeneration measures for threatened species were proposed.